Strategi penanganan permukiman kumuh di Kampung Jawa, Distrik Manokwari Barat, Kabupaten Manokwari - Jamaludin Ugar; Syafrudin Raharjo; Bambang Nugroho (Cassowary, 2023)
Kampung Jawa is one of the slums in Manokwari Regency, West Papua Province and the Regency government claims the area as a slum area with regional regulations in 2015 and 2020. Over time; The area is growing so rapidly because, the location of Kampung Jawa is in the economic strategic area of ​​Manokwari Province, namely the Center for Trade, Trade and Services, West Regency of Manokwari Province. The physical development that occurs in the area without any planning process for the wild area of ​​Manokwari Province, so that it has an impact on storage activities. so that the arrangement of buildings in this area is inadequate. Worries about a condition if there is no immediate response by stakeholders (government, community, and private sector) so that it will have a massive environmental degradation impact on the coastal area of ​​Wosi Bay. The aims of this study were 1) to determine the characteristics of the development of slum settlements and the level of slums in Kampung Jawa, Teluk Wosi Area, West Manokwari District; 2) Formulating a strategy for developing slum settlements in Kampung Jawa, Teluk Wosi Area, West Manokwari District; 3) formulating or planning an alternative concept of structuring the coastal area of ​​Kampung Jawa that is good, sustainable and in line with the Manokwari Regency Regulations, as well as applicable laws and regulations. This research is descriptive and uses two methods of analysis, namely quantitative to answer the first problem and qualitative to answer the second and third problems. The results showed that the settlement of Kampung Jawa was included in the typology of the village with the heavy category of slums. The results of the SWOT analysis obtained alternative handling strategies, namely the strategies generated based on a combination of two elements of strength (internal) and elements of opportunity (external) to overcome existing weaknesses and threats. The concept of structuring the area is carried out by applying the concept of a waterfront city with physical and non-physical development based on the original characteristics and functions of Kampung Jawa.